2021
DOI: 10.1038/s41420-021-00616-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning with digital holographic microscopy discriminates apoptosis and necroptosis

Abstract: Regulated cell death modalities such as apoptosis and necroptosis play an important role in regulating different cellular processes. Currently, regulated cell death is identified using the golden standard techniques such as fluorescence microscopy and flow cytometry. However, they require fluorescent labels, which are potentially phototoxic. Therefore, there is a need for the development of new label-free methods. In this work, we apply Digital Holographic Microscopy (DHM) coupled with a deep learning algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Pre-trained CNNs have already provided excellent results to detect cell death or differentiation for adherent cells on a 2D surface 27,29,35 . Interestingly, such CNNs did not provide a better accuracy than ours (91.2%) while requiring larger computing times (See Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-trained CNNs have already provided excellent results to detect cell death or differentiation for adherent cells on a 2D surface 27,29,35 . Interestingly, such CNNs did not provide a better accuracy than ours (91.2%) while requiring larger computing times (See Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is one of the best characterized cell death modalities. It is mediated by the kinase activities of receptor interacting protein kinase-1 (RIPK1) and RIPK3 and activation of the executioner protein mixed lineage kinase domain-like (MLKL), leading to rapid membrane permeabilisation and release of intracellular contents into the extracellular environment (46)(47)(48)(49)(50). Although it was initially shown that necroptotic cells do not induce pro-inflammatory responses (51,52), several recent reports indicate that necroptotic cancer cells are immunogenic (Figure 2) and can induce effective anti-tumor immune responses (55,61).…”
Section: Necroptosismentioning
confidence: 99%
“…This distinction might be used to morphologically distinguish ferroptosis from other regulated cell death modalities by using different microscopic methods, including those based on artificial intelligence. 28 …”
Section: Characteristics Of Ferroptosismentioning
confidence: 99%
“…This distinction might be used to morphologically distinguish ferroptosis from other regulated cell death modalities by using different microscopic methods, including those based on artificial intelligence. 28 Open access conditions contribute to different physiological processes. They are released (or exposed on the outer surface of the plasma membrane) when a cell is damaged or dying.…”
Section: Morphological Changes During Ferroptosismentioning
confidence: 99%